Strategic Planning In Small Enterprises on Shaping the Competitive Advantage of Boutique Hotels in Sabah and Sarawak - Wei Liang, Cheing (2018)
The relevance of strategic planning in small enterprises presents a mixed outcome in the literature. Lack of key decision contents indicators hinder strategic planning among small enterprises owner-managers who depend on their intuition and experience in making strategic decisions. Moreover, the development of strategic planning contents from a unidimensional versus multidimensional approach remains inconclusive. At present, there is minimal knowledge on the applicability of planning dimensions which contribute to small enterprises competitive advantage. The aim of this study was to determine the relevance of strategic planning in boutique hotels through key planning topics and coordination as the base to develop key decision contents indicators A novel strategic planning content framework for small enterprises was introduced which allowed inquiry into unexamined aspects focusing on a contentoriented, emergent approach as opposed to process-deliberate. These included decision content, planning formality, owner-manager influence, strategic analysis framework and internal-external aspects. Through a case study approach, semi-structured interviews were conducted with owner-managers of nine boutique hotels located throughout Sabah and Sarawak. Findings suggest strategic planning is relevant for boutique hotels where decision indicators relate to profits, marketing, operations and facilitated by briefing and proposal. Multidimensional approach design is more suitable and all four planning dimensions are pertinent except strategic analysis framework. Strategic planning is considered an option, not a necessity and decision contents are informal and intuitive. The strategic planning framework for small enterprises is an original contribution of this study focusing on decision contents and planning dimensions. Instant-Messaging Applications, closer collaboration with online travel agents, retention of key employees and knowledge acquisition should guide boutique hotels to remain sustainable. Small enterprises do differ significantly from larger enterprises in their strategic planning practice and future research should consider multidimensional approach.